2022
DOI: 10.1093/pm/pnac140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Percutaneous and Transcutaneous Electrical Nerve Stimulation on Endogenous Pain Mechanisms in Patients with Musculoskeletal Pain: A Systematic Review and Meta-Analysis

Abstract: Objectives The main aim was to determine the effects of percutaneous (PENS) and transcutaneous (TENS) electrical nerve stimulation on endogenous pain mechanisms in patients with musculoskeletal pain. Design A systematic review and meta-analysis. Methods The search was conducted on March 1, 2022, in EMBASE, CINAHL, PubMed, PEDro, Cochrane Library, Web of Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 111 publications
0
6
0
Order By: Relevance
“…First, it is possible that PENS could reduce nerve excitability (the median nerve) by altering nociceptive input and reducing neurogenic inflammation or ectopic discharge (García‐Collado et al, 2022). A recent meta‐analysis has concluded that PENS seems to be able to modulate altered pain processing by decreasing pain sensitivity and activating conditioning pain modulation, although further studies are needed to confirm this (Lagos et al, 2022). In fact, preliminary data suggest that manual therapy can modulate pain processing (Arribas‐Romano et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…First, it is possible that PENS could reduce nerve excitability (the median nerve) by altering nociceptive input and reducing neurogenic inflammation or ectopic discharge (García‐Collado et al, 2022). A recent meta‐analysis has concluded that PENS seems to be able to modulate altered pain processing by decreasing pain sensitivity and activating conditioning pain modulation, although further studies are needed to confirm this (Lagos et al, 2022). In fact, preliminary data suggest that manual therapy can modulate pain processing (Arribas‐Romano et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of SD of the difference, we imputed from other data reported in the study: (1) using other measures reported in the study (e.g., confidence intervals and p values, following the principles described in Chapter 6.5.2.2 of the Cochrane Handbook) [36]; or, if that was not possible, (2) using the correlation coefficient of the most similar study included (following the principles described in Chapter 6.5.2.8 of the Cochrane Handbook) [36]; or if that was not possible, (3) using a conservative correlation coefficient of 0.5 [37]. This methodology has been performed in other meta-analyses [38].…”
Section: Data Synthesismentioning
confidence: 99%
“…Regarding current density, five applied a current density of 0.028 mA/cm 2 [21,24,41,45], two applied 0.04 mA/cm 2 [19,44], nine applied 0.057 mA/cm 2 [5,25,26,40,46,47,50,57], and one applied 0.1 mA/cm 2 [53]; the rest of the studies did not report current density. Regarding stimulation time, one applied tDCS for 7 min [38], three for 10 min [23,52], five for 15 min [21,24,41,45,57], eighteen for 20 min [5,9,19,22,26,[42][43][44][47][48][49][50][51][53][54][55][56], and one for 40 min [46]. Most studies conducted single treatment sessions [5,17,19,21,23,25,26,…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Despite its potential benefits in pain management, the precise indications for PENS, as well as the most effective treatment parameters, remain topics of discussion and investigation within the medical community. Additionally, comparative studies evaluating PENS against other therapeutic modalities are limited, leaving uncertainties about its relative efficacy and place in treatment algorithms [ 189 , 193 , 194 ]. To address these gaps in knowledge, future research efforts should prioritize well-designed studies that investigate the clinical utility of PENS across various pain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…To address these gaps in knowledge, future research efforts should prioritize well-designed studies that investigate the clinical utility of PENS across various pain conditions. These studies should aim to delineate the specific patient populations most likely to benefit from PENS, identify optimal stimulation parameters, and compare its efficacy and safety to other established treatments [ 189 , 193 , 194 ]. Furthermore, incorporating mechanistic studies to elucidate the underlying pathways through which PENS exerts its therapeutic effects can provide valuable insights into its mode of action and potential advantages over alternative interventions.…”
Section: Introductionmentioning
confidence: 99%